2006
DOI: 10.1557/proc-0963-q10-57
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Carbon Nanotube Thin-Film Transistors with Transfer-Print Assembly

Abstract: Abstract:Conditions for the transfer printing of patterned carbon nanotube (CNT) films, along with a Au-gate, a poly methylmethacrylate (PMMA) dielectric layer and Au source-drain electrodes have been developed for the fabrication of thin-film transistors on a polyethylene terephthalate (PET) substrate. Chemical vapor deposition (CVD) grown CNTs were patterned using a photolithographic method.Transfer printing was used to fabricate devices having both top gate and bottom gate configurations. Replacement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In the post-growth method, CNT thin films are selectively removed after growth with a transfer printing method. We have previously shown that CNTs can be transferred from SiO 2 to thermoplastics (polyterephthalate (PET)) [10,11] and metallic substrates (Au and Pd) [12]. This means that pristine CNTs can be patterned by printing onto stamps made from these materials, thus a transfer printing method using stamps of PET and Au was developed.…”
Section: B Patterning Cnt Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the post-growth method, CNT thin films are selectively removed after growth with a transfer printing method. We have previously shown that CNTs can be transferred from SiO 2 to thermoplastics (polyterephthalate (PET)) [10,11] and metallic substrates (Au and Pd) [12]. This means that pristine CNTs can be patterned by printing onto stamps made from these materials, thus a transfer printing method using stamps of PET and Au was developed.…”
Section: B Patterning Cnt Thin Filmsmentioning
confidence: 99%
“…Controlled placement of patterned CNT films can achieved by transfer printing [10,11] when proper differential adhesion exists between the CNT/SiO 2 substrate and device substrate. This is ensured by using the release layer mentioned in previous section.…”
Section: C Controlled Placement Of Patterned Cnt Thin Filmsmentioning
confidence: 99%
“…These techniques have produced high-quality, light-weight, flexible devices. [8][9][10][11] This process has the potential to be scaled-up for roll-to-roll manufacturing. 12,13 Transfer printing relies primarily on differential adhesion where a printable layer deposited (and possible patterned) onto one substrate (the transfer substrate) is pressed against a second substrate (the device substrate).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of materials have been utilized in the fabrication of thin-film transistors (TFT) and mechanical resonators. Thin-film transistors with active layers of Pentacene (Pn), poly(3-hexylthiophene) (P3HT), carbon nanotube mats (CNTM), graphene and silicon (Si) nano-ribbons have all been fabricated with a polymethylmethacrylate (PMMA) dielectric layer on a polyethylene terephthalate (PET) substrate [1,2,3,4]. Figure 1 shows optical micrographs of (a) CNTM, (b) graphene and (c) Si nano-ribbon devices.…”
mentioning
confidence: 99%